New subfamilies and a new genus and species of Melithaeidae (Coelenterata: Octocorallia: Alcyonacea) with comparative data on the structure of both melithaeid and subergorgiid axes - Alderslade, Philip (Zootaxa, 2006)
Asperaxis karenae, a new genus and new species of the gorgonian family Melithaeidae, is described. The coenenchymal sclerites of the new genus bear similarities to those of Acabaria, but the axis is quite different from that which is characteristic of the family. The axial sclerites are rods and sticks, often sinuous and branched, with simple, sparse, tubercles. The internodes may be whole or partial, and are not clearly delimited from the internodes. A new subfamily, Asperaxinae, is proposed to accommodate any taxa with the new axial characters, and the Melithaeinae for the existing nominal taxa. The structure of both axial forms and the subergorgiid axis are illustrated with scanning electron micrographs.